PREDICTIVE FACTORS FOR ANXIETY AND DEPRESSION AMONG HEALTHCARE WORKERS AT VIETNAM NATIONAL UNIVERSITY HOSPITAL, HANOI IN THE CONTEXT OF THE COVID-19 PANDEMIC: A CROSS-SECTIONAL STUDY (Vietnam Journal of Community Medicine, 2026)
Objective: To identify factors associated with stress, anxiety, and depression among healthcare workers at Hanoi National University Hospital. Methods: A cross-sectional study design was employed. The DASS-21 instrument was used to assess mental health status. Multivariable logistic regression models were applied to determine associations with demographic and occupational factors. Results: Male gender was associated with an increased risk of anxiety (OR = 2.1; 95% CI: 1.1–4.1) and depression (OR = 2.0; 95% CI: 1.02–4.02). Staff members had a 4.2-fold higher risk of depression compared to those in leadership positions (95% CI: 1.6–11.5; p = 0.005). Permanent employees had a 3.0-fold higher risk of anxiety compared to contract workers (95% CI: 1.3–6.6; p = 0.009). Low income (< 5 million VND) increased the risk of depression by 2.7 times (p = 0.049). No statistically significant associations were found between the studied factors and stress (p > 0.05). Conclusion: Mental health status among the study population was associated with male gender, staff position, permanent employment status, and low income. These findings provide a basis for developing psychological support policies and improving working conditions for high-risk groups within the institution.
Keywords: Stress, Anxiety, Depression, Logistic regression, Healthcare workers.